The effect of public expenditures on economic growth of Kosovo: An econometric analysis - Florije Miftari; Nakije Kida; Nuhi Shala (Economics, Management and Sustainability, 2021)
Public spending as an important component of the composition of GDP has an impact on economic growth and development. The main purpose of this paper is to analyze the effects of disaggregated public expenditures, to measure the impact of current expenditures, transfers and subsidies, and capital expenditures as part of total government expenditures on economic growth and development of the Republic of Kosovo. To achieve the main goal of the paper was used the multiple linear regression model (OLS) and Pearson. The regression model has been modified and adapted to measure the regression of public spending on economic growth in Kosovo. The data used in the paper are secondary and collected from the Ministry of Finance of Kosovo, Agency of Statistics, and the Tax Administration of Kosovo. Data processing was done with SPSS. The results of the analysis show that the trend of Kosovo public spending for the analyzed period is increasing. According to Pearson correlation analysis, the results show that current public spending; transfers, and subsidies have a strong positive correlation to Gross Domestic Product. Whereas capital (investment) expenditures have a weaker positive correlation with GDP. The results of OLS regression, in our case, did not show the significance of independent variables, which means that the pubic expenses do not have an impact on economic growth in Kosovo.